Profile of aluminum phosphide poisoning in a tertiary care institute in the sub-Himalayan region - Sharma, Tarun (J Family Med Prim Care, 2018)
CONTEXT: Aluminum phosphide (ALP) is a highly toxic agricultural fumigant pesticide commonly implicated in poisoning. AIM: The aim of the study was to study the profile of patients presenting with ALP poisoning in Dr. RPGMC Kangra, Tanda, Himachal Pradesh. SETTINGS AND DESIGN: This was a retrospective study conducted in the Department of Medicine at Dr. RPGMC Kangra, Tanda, Himachal Pradesh, from August 2011 to January 2014. MATERIAL AND METHODS: Case record forms of 117 patients were reviewed and analyzed. Data were collected for sociodemographic and clinical parameters. Outcome of patients was recorded as expired and improved. All the patients were managed symptomatically. STATISTICAL ANALYSIS: Statistical analysis was performed using SPSS version 15. P < 0.05 was considered statistically significant. RESULTS: Out of the total 117 patients included in the study, 61 (52.1%) were males and 56 (47.1%) were females. Mean age ± standard deviation of presentation was 30.9 ± 12.2 years. About 70% of the patients were from rural background. Out of the total 117 patients, 68 (58.1%) patients had expired and 49 (41.9%) had improved. Most of the patients in the expired group consumed ALP in tablet form (54.7% of the total). Nearly 57% of the patients had leukocytosis at presentation and <5% had leukopenia. The mean pulse rate and mean systolic blood pressure in the expired group were 116.24 ± 14.3 per minute and 89.9 ± 16.83 mmHg which was statistically significant. The mean change in creatinine value (ΔCr) in the expired group was 1.03 ± 0.36 which was statistically significant. CONCLUSIONS: The prognosis of the patients can be anticipated on assessing the cardiac status and mean change in creatinine value (ΔCr) at the time of admission.